2013
DOI: 10.1056/nejmsa1213829
|View full text |Cite|
|
Sign up to set email alerts
|

Achievement of Goals in U.S. Diabetes Care, 1999–2010

Abstract: Although there were improvements in risk-factor control and adherence to preventive practices from 1999 to 2010, tobacco use remained high, and almost half of U.S. adults with diabetes did not meet the recommended goals for diabetes care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

35
740
15
20

Year Published

2013
2013
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 902 publications
(831 citation statements)
references
References 32 publications
35
740
15
20
Order By: Relevance
“…Health insurance was associated with taking statins and LDL‐C control, a finding supported by Mann et al with regard to statin use and by Ali et al in a national study of LDL‐C control improvement 13, 14. Inadequate insurance coverage itself could have been a barrier to obtaining statins.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Health insurance was associated with taking statins and LDL‐C control, a finding supported by Mann et al with regard to statin use and by Ali et al in a national study of LDL‐C control improvement 13, 14. Inadequate insurance coverage itself could have been a barrier to obtaining statins.…”
Section: Discussionmentioning
confidence: 69%
“…Although statin use has increased in the United States since 2003,7, 11 studies have reported underutilization of the medication12 and suboptimal LDL‐C control in persons with diabetes mellitus 7, 13. Lower statin use by blacks and women has been observed in general primary‐care populations,14, 15, 16, 17, 18, 19 but no studies have examined patterns of statin use by race‐sex groups among individuals with diabetes mellitus in the United States.…”
Section: Introductionmentioning
confidence: 99%
“…There have been several prior studies examining quality of care of patients with diabetes mellitus, which have generally been focused on goal attainment of cardiovascular risk factors (eg, cholesterol, hemoglobin A1c, blood pressure, and body mass index) 28, 29, 30, 31, 32. For example, an analysis of the National Health and Nutrition Examination Survey survey of patients with self‐reported diabetes mellitus showed that 87% of patients had a hemoglobin A1c <9%, 73% and 71% reported having an eye and foot examination in the prior year, respectively, and 72% reported having a blood pressure <140/90 31.…”
Section: Discussionmentioning
confidence: 99%
“…Despite some improvements 5, the quality of diabetes care has not yet reached the level recommended by the practical guidelines developed on the basis of state‐of‐the‐art scientific evidence (‘evidence–practice gap’) 6, although the gap is gradually decreasing 5, 7. To reduce the ‘evidence–practice gap’ in diabetes care, effective, evidence‐based interventions should be developed.…”
Section: Introductionmentioning
confidence: 99%